Review article: Early steroid administration for traumatic haemorrhagic shock: A systematic review. (8th November 2022) - Hogarty, Joseph P; Jones, Morgan E; Jassal, Karishma; Hogarty, Daniel T; Mitra, Biswadev; Udy, Andrew A; Fitzgerald, Mark C
Abstract: Haemorrhagic shock after trauma is a leading cause of death worldwide, particularly in young individuals. Despite advances in trauma systems and resuscitation strategies, mortality from haemorrhagic shock has not declined over the previous two decades. A proportion of shocked trauma patients may experience a deficiency of cortisol relative to the severity of their injury. The benefit of exogenous steroid administration in patients suffering haemorrhagic shock as a result of injury is unclear. A systematic review of four databases (Ovid Medline, Ovid Embase, Cochrane, Scopus) was undertaken. Inclusion and exclusion criteria were pre‐determined and two reviewers independently screened the articles with disagreements arbitrated by a third reviewer. The primary outcome variable was 28‐day mortality. Quality of studies were assessed using the Cochrane‐risk‐of‐bias (RoB 2) tool. Of the 2919 studies yielded by the search strategy, 1274 duplicates were removed and 1645 screened on title and abstract. After the full text of 33 studies were assessed, two articles were included. Both studies were over 30 years old with small numbers of participants and with primary outcomes not including mortality. Of the data available, no statistically significant difference in mortality was detected. Hospital length of stay, reversal of shock or adverse events were not reported. Both studies were at risk of bias. There are no high quality or recent studies in the English literature investigating the use of steroids for haemorrhagic shocked trauma patients. PROSPERO: CRD42021239656. Abstract : Earlysteroid administration for traumatic haemorrhagic shock: A systematic review